International Financial Management in Practice: The Case of Chinese Companies - Xuezhu Ruan; Timofey Mazurchuk (Communications of International Proceedings, 2022)
Financial management in the company must create an effective system for the movement of financial resources, which are based on the management of economic indicators, such as revenue, cost, profit and profitability of the company. The goal of financial management is to make a profit and achieve maximum results for the company. The annual balance sheet and financial statements of the company's activities allow us to find out whether the company has a profit or is it unprofitable, to determine the business activity of the business, to calculate the indicators of profitability and liquidity. Thus, conducting financial analysis and developing plans will help shape the company's activities for the future.
Keywords: component: foreign investment; finance; risk; financial management.